2016
DOI: 10.1111/mec.13700
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and variation in social aggression by queens of the harvester ant Pogonomyrmex californicus

Abstract: A key requirement for social cooperation is the mitigation and/or social regulation of aggression towards other group members. Populations of the harvester ant Pogonomyrmex californicus show the alternate social phenotypes of queens founding nests alone (haplometrosis) or in groups of unrelated yet cooperative individuals (pleometrosis). Pleometrotic queens display an associated reduction in aggression. To understand the proximate drivers behind this variation, we placed foundresses of the two populations into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 78 publications
0
24
0
Order By: Relevance
“…the number of genes that are differentially expressed) differences in responses to environmental pressures in a variety of organisms, including plants, insects, molluscs, crustaceans, and fish (Ye et al ., 2014; Zhao et al ., 2014; Cañas et al ., 2015; Faddeeva et al ., 2015; Cheng, Hui, & Sha, 2019; Jesus et al ., 2019). In recent years, DGE studies in social insects have highlighted a number of genes that are involved in colony organisation and adaptation to environmental constraints (Ferreira et al ., 2013; Helmkampf et al ., 2016; Lucas, Romiguier, & Keller, 2017; Willot et al ., 2018; Holman et al ., 2019). However, such studies remain fairly rare, and many taxa are currently ignored.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…the number of genes that are differentially expressed) differences in responses to environmental pressures in a variety of organisms, including plants, insects, molluscs, crustaceans, and fish (Ye et al ., 2014; Zhao et al ., 2014; Cañas et al ., 2015; Faddeeva et al ., 2015; Cheng, Hui, & Sha, 2019; Jesus et al ., 2019). In recent years, DGE studies in social insects have highlighted a number of genes that are involved in colony organisation and adaptation to environmental constraints (Ferreira et al ., 2013; Helmkampf et al ., 2016; Lucas, Romiguier, & Keller, 2017; Willot et al ., 2018; Holman et al ., 2019). However, such studies remain fairly rare, and many taxa are currently ignored.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Several transcriptome analyses have been performed during caste differentiation in hymenopteran species, all of which suggested that social cues were crucial modulators of gene expression changes (Toth & Rehan, ). For example, huge transcriptomic differences were observed among different social contexts in the ants Pogonomyrmex californicus and Cardiocondyla obscurior (Helmkampf, Mikheyev, Kang, Fewell, & Gadau, ; Schrader, Simola, Heinze, & Oettler, ). Moreover, the expression levels of nutrition‐sensitive genes involved in caste determination changed in different conditions with/without reproductive castes in the ant Diacamma sp.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on two previously published studies on the transcriptomic basis for nest founding behaviour in paper wasps and fire ants. These were the only studies available at the time when we designed the experiment that explored global changes of gene expression associated with dominance behaviour in foundresses of social insects (but see Helmkampf et al 2016 for another more recent study on the transcriptomics of ant foundresses). The first study (study “A”, Toth et al 2014 ) investigated the global patterns of gene expression associated with dominance hierarchies in Polistes metricus , a paper wasp closely related to P. dominula .…”
Section: Methodsmentioning
confidence: 99%